A vital city and revitalization processes - Hajduga, Piotr (Miasto witalne a procesy rewitalizacji, 2020)
Polish urban centres have been going to great lengths to reactivate the vitality of space, community, economy, and the environment in recent years. The term ‘revitalization’ is used in a broad sense that is adapted to the roots of the problems considered most acute in a given territorial unit. At the same time, it could seem that, in many cases, the measures taken focus on rather superficial issues related to image or on remedying the noticeable symptoms of the problems. What becomes a central challenge is the redefinition of the operating mechanism of a city, i.e. the mechanism where various processes are in harmony with each other, the actions taken by local entities are characterized by synergy, competition for resources is rationalized, and the operation of the entire system is determined by original and creative development directions which integrate local entities and include the city into the network of ties with the surroundings. The detailed discussions described in this paper concern the vital city and urban space revitalization processes
Biblioteka Regionalisty, 2020, Nr 20, s. 38-48
Keywords: revitalization; vital city; urban space; rewitalizacja; miasto witalne; przestrzeń miejska